Being an oncologist in China: my notes about cancer treatment in China - Wu, Aiwen (Chinese Journal of Cancer Research; Vol 25, No 3 (June 28, 2013): Chinese Journal of Cancer Research, 2013)
Today I read a popular article about the management of cancers in China (1). Although written by foreign doctors, it does utter some ‘unspeakable helplessness’, as commented by a netizen. Many unique dilemmas do exist, and must be honestly faced by government, industry, doctors, patients, and the society.